Pengembangan Modul Cetak Pengolahan Sampah Basah Berbantuan Maggot BSF dan Efektivitasnya dalam Meningkatkan Pengetahuan Lingkungan Siswa - Muhammad Ainurridho; Fatchur Rochman; Vivi Novianti; Khairil Asnan Haedar (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The environment is defined as a set of aspects in the form of physical, chemical and biological as well as social factors that have a direct or indirect relationship to living things and human activities in the short and long term. However, the environment can experience various problems, one example is environmental damage by causing waste in the environment. One of the reasons for the waste generated by the community is their lack of knowledge about the environment. It was proven in preliminary research at SMA Negeri 11 Pinrang, the results of the initial analysis using students' environmental knowledge questions were still low with an overall result of 43.73. These results indicate that there are still many students who do not know environmental topics and problems, especially waste and its processing, so they are lazy about disposing of waste according to the server and processing the waste, especially wet waste. This research is development research referring to Plomp and Nieven's development design and conducting a quasi-experiment using the PjBL model in class X at SMA Negeri 11 Pinrang. The research results show that the printed module has a practicality value of 91.1% in the very practical category so it is suitable for use in the learning process. The average pretest result for the experimental class was 50.8 in the low category after learning using printed modules and the PjBL model and the posttest was 88 in the very high category and experienced an increase of 37.2%. The average pretest result for the control class was 44.26 in the low category after learning only using the PjBL model and the posttest was 79.6 in the high category and experienced an increase of 35.34%. Therefore, it can be concluded that the printed module is practical and effective in the experimental class with an N-Gain value of 0.75.